Lexical Cohesion in Conversational Discourse on Sports Media: An Analysis of CBS Sports Golazo’s UCL Today Moments Playlist - Wildan Rayyan Ramadhan; Cipto Wardoyo; Agry Pramita (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study analyzes the use of lexical cohesion in spoken discourse, particularly within the digital sports media context of CBS Sports Golazo’s UCL Today Moments playlist. Lexical cohesion, as defined by Cutting (2005), encompasses devices such as repetition, synonymy, superordinate terms, and general words, which contribute to the coherence and clarity of spoken interaction. Utilizing a descriptive qualitative method, this research analyzed five episodes from the playlist, totaling approximately 45 minutes of conversational data. The findings reveal that repetition is the most frequently used cohesion device (37%), followed by general words (25.9%), synonyms (24.1%), and superordinate terms (13%). These patterns highlight how speakers naturally employ lexical cohesion to emphasize meaning, avoid redundancy, and maintain discourse continuity in informal, spontaneous settings. The study also underscores the functional significance of lexical cohesion in managing the flow and coherence of talk show interactions. By focusing on two-way digital conversations, this research fills a gap in previous studies that primarily addressed one-directional or written discourse, offering new insights into how lexical cohesion operates in real-time, dialogic communication.